2002
DOI: 10.1002/path.1166
|View full text |Cite
|
Sign up to set email alerts
|

p63 immunoreactivity in lung cancer: yet another player in the development of squamous cell carcinomas?

Abstract: The p63 protein, a member of the p53 family of nuclear transcription factors, is characterized by different capabilities of transactivating reporter genes, inducing apoptosis, and functioning as dominant-negative agent. This study evaluated the prevalence and prognostic implications of p63 immunoreactivity in 221 patients with stage I non-small cell lung carcinoma (NSCLC) and in 57 patients with stage I-IV neuroendocrine tumours (NET). The results were correlated with the tumour proliferative fraction, the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
137
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 44 publications
17
137
2
Order By: Relevance
“…37 Some reported that p63 was expressed in pulmonary squamous cell carcinoma but not in small cell carcinomas, 37,38 whereas others reported that large cell neuroendocrine carcinoma and small cell carcinoma had p63 expression. 39,40 The reported differences of frequency of p63 expression in small cell carcinoma may be due to different identification methods for positive cells. Zhang et al 38 reported that they defined the tumor as p63-negative if less than 10% of tumor cells were stained.…”
Section: Discussionmentioning
confidence: 99%
“…37 Some reported that p63 was expressed in pulmonary squamous cell carcinoma but not in small cell carcinomas, 37,38 whereas others reported that large cell neuroendocrine carcinoma and small cell carcinoma had p63 expression. 39,40 The reported differences of frequency of p63 expression in small cell carcinoma may be due to different identification methods for positive cells. Zhang et al 38 reported that they defined the tumor as p63-negative if less than 10% of tumor cells were stained.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is conceivable that activation (or induction) of p63 may divert the intraductal neoplastic cells towards a more mature, metaplastic process. As in other organs, 3,9,[23][24][25] DNp63 is a reliable marker of squamous differentiation also in pancreatic carcinoma. Among invasive carcinomas of the pancreas, DNp63 immuno-expression is largely limited to the areas of squamous differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…As the key molecule of the epithelial stratification program, 13 DNp63 expression is highly specific for squamous differentiation in neoplasia, and is usually not detected in nonsquamous carcinomas such as adenocarcinoma, small cell carcinoma or mesothelioma and others. 3,9,21,[23][24][25][26] This is valuable in the differential diagnosis of poorly differentiated malignant tumors of undetermined origin.…”
mentioning
confidence: 99%
“…34,35 In each tumor, the sarcomatoid and epithelial components were assessed separately, recording the percentage of neoplastic cells immunoreactive for the different antigens in either components.…”
Section: Immunohistochemistrymentioning
confidence: 99%